Measurement of IgG4 in bile: a new approach for the diagnosis of IgG4-associated cholangiopathy - Vosskuhl, K.; Negm, A. A.; Framke, T.; Weismüller, T.; Manns, M. P.; Wedemeyer, H.; Plentz, R. R.; Wedemeyer, J.; Lankisch, T. O. (Endoscopy, 2012)
Background and study aims: Immunoglobulin G4 (IgG4)-associated cholangitis (IAC) is difficult to diagnose because on cholangiography the associated biliary tract strictures cannot be differentiated from cholangiocarcinoma or primary sclerosing cholangitis (PSC). Serum IgG4 levels show a low sensitivity and specificity and are unreliable, particularly in patients with related diseases such as PSC. As IAC takes place at the biliary epithelium, we hypothesized that IgG4 measurement in bile may have higher sensitivity compared with serum. Methods: Bile and serum samples were collected during cholangiography in 67 patients, including 23 patients with PSC, 25 with cholangiocarcinoma, 14 with choledocholithiasis, and five with IAC. IgG4 was measured in both bile and serum.Results: Bile IgG4 levels were markedly elevated in patients with IAC compared with patients with other biliary disorders. Whereas elevated serum IgG4 levels were found both in patients with PSC and IAC, biliary IgG4 levels were only increased in patients with IAC.Conclusions: The study demonstrates that bile IgG4 measurement is possible and may help to distinguish IAC from other diseases.